2023
DOI: 10.1091/mbc.e23-05-0205
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response of the endoplasmic reticulum supports mitochondrial biogenesis by buffering nonimported proteins

Abstract: Almost all mitochondrial proteins are synthesized in the cytosol and subsequently targeted to mitochondria. The accumulation of non-imported precursor proteins occurring upon mitochondrial dysfunction can challenge cellular protein homeostasis. Here we show that blocking protein translocation into mitochondria results in the accumulation of mitochondrial membrane proteins at the endoplasmic reticulum, thereby triggering the unfolded protein response (UPRER). Moreover, we find that mitochondrial membrane protei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Interestingly, a recent systematic study with libraries of GFP-tagged mitochondrial proteins reported the accumulation of a number of mitochondrial precursor proteins on the ER upon mitochondrial dysfunction, most of which being hydrophobic membrane proteins (Shakya et al, 2021 ). Moreover, mitochondrial dysfunction leads to the accumulation of mitochondrial proteins on the ER and induces the unfolded protein response of the ER (Coyne et al, 2023 ; Knöringer et al, 2023 ; Sarkar et al, 2022 ; Xiao et al, 2021 ). Upon depletion of Mdm34 in Δtom70 cells, the affinity-purified ER and mitochondrial fractions partially lost their characteristic protein composition, indicating that the ER-mitochondria contact sites are essential for organellar protein identity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a recent systematic study with libraries of GFP-tagged mitochondrial proteins reported the accumulation of a number of mitochondrial precursor proteins on the ER upon mitochondrial dysfunction, most of which being hydrophobic membrane proteins (Shakya et al, 2021 ). Moreover, mitochondrial dysfunction leads to the accumulation of mitochondrial proteins on the ER and induces the unfolded protein response of the ER (Coyne et al, 2023 ; Knöringer et al, 2023 ; Sarkar et al, 2022 ; Xiao et al, 2021 ). Upon depletion of Mdm34 in Δtom70 cells, the affinity-purified ER and mitochondrial fractions partially lost their characteristic protein composition, indicating that the ER-mitochondria contact sites are essential for organellar protein identity.…”
Section: Discussionmentioning
confidence: 99%
“…We regard it as likely that both the membrane and the soluble proteins are targeted to the ER surface by the signal recognition particle and by chaperones of the ER surface such as Ydj1, Djp1, and Get3, which interact with mitochondrial precursor proteins (Caplan et al, 1992 ; Costa et al, 2018 ; Drwesh et al, 2022 ; Gamerdinger et al, 2015 ; Hansen et al, 2018 ; Xiao et al, 2021 ). Intriguingly, proximity-based ribosome profiling revealed that many mitochondrial proteins are synthesized by ER-bound ribosomes (Jan et al, 2014 ; Knöringer et al, 2023 ). It is not known whether this ER association of mitochondrial precursors is an unavoidable mislocalization owing to the fact that the cytosolic targeting machinery erroneously interprets some mitochondrial proteins as ER proteins or, which seems more likely, that eukaryotic cells use the ER as a buffer to absorb potentially harmful precursor proteins to reduce their toxic potential (Coyne et al, 2023 ; Knöringer et al, 2023 ; Nowicka et al, 2021 ; Sutandy et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, two recent reports suggest that the stress response of the ER, the unfolded protein response (UPR ER ), affects mitochondrial biogenesis at the level of RNA and non-imported preproteins. Knöringer et al [ 156 ] describe that the accumulation of un-imported mitochondrial protein precursors in yeast triggers the UPR due to their ER localization. This is in line with earlier reports that show a tight interweaving of the stress responses of the two organelles, also in mammalian cells [ 157 , 158 ].…”
Section: The Long (Or Short) Post-translational Journey To Mitochondriamentioning
confidence: 99%